Utilization of Cigarette Butt Filter Waste as an Alternative Growing Medium in Hydroponic Systems - Sabilillah, Nara Abdullah Sufi Al Amin; Rabbani, Raffael Rayya; Nurrahmawati, Dini (Indonesian Journal of Advanced Research, 2026)
Cigarette packaging contains cellulose acetate, which is difficult to decompose and pollutes the environment. This study aims to utilize this waste as an alternative growing medium in hydroponic systems. The experimental method was applied to water spinach (Ipomoea aquatica) plants by comparing its performance with Rockwool. The implementation stages included physical cleaning, sterilization with 70% alcohol, and boiling to remove harmful chemical residues. Based on observations over 26 days, the Independent Sample T-test results showed a significant value of 0.86 (p > 0.05). This indicates that there was no significant difference in plant height and number of leaves. The implication is that cigarette butt waste has been proven to be effective as a growing medium equivalent to Rockwool.